Effects of acute low intensity aerobics and blueberry juice on arterial stiffness in young adults - Ruisi Wu; Huali Yu; Jiayuan Xu; Zhiqiang Tan; Yongsheng Lan; Dongfang Shi (npj Science of Food)
Abstract Arterial stiffness, a cardiovascular disease (CVD) predictor starting from youth, is under-researched in young adults. Low-intensity aerobic exercise (LAE) is generally more accessible than higher-intensity exercise and may be more sustainable for young individuals. Blueberries, renowned for vascular health benefits, may reduce arterial stiffness. This study examines the effects of LAE and blueberry juice on arterial stiffness in 48 young adults. Participants were randomized into LAE, low-, mid-, or high-volume blueberry juice (LB, MB, HB), LAE + LB, LAE + MB, LAE + HB, and control groups. Arterial stiffness was measured at baseline and at 15-, 30-, 45-, and 60 min post-intervention. Blood samples were collected pre-intervention and 30-min post-intervention for metabolomic analysis. Repeated ANOVA revealed LAE + MB significantly reduced arterial stiffness. Metabolomic analysis revealed changes in linoleic acid, sphingolipid, phenylalanine, nicotinate and nicotinamide, glycerophospholipid, and lysine degradation metabolic pathways. These findings suggest a feasible exercise-diet strategy for CVD prevention in young adults and provide metabolic insights into the mechanisms.